Hemoperitoneum Secondary to Spontaneous Rupture of a Retroperitoneal Varix. (3rd August 2017) - Eichele, Derrick D.
Abstract : Hemoperitoneum due to a ruptured retroperitoneal varix is an exceedingly rare condition and a poor prognostic sign with catastrophic and life-threatening complication of portal hypertension. We present a unique case of a 56-year-old female with cirrhosis secondary to primary sclerosing cholangitis who presented with acute abdominal pain and hypovolemic shock prior to a cardiac arrest following a ruptured retroperitoneal varix without prior esophageal varices and a newly identified intrahepatic cholangiocarcinoma. The clinical presentation with abdominal pain and hemorrhagic shock is consistently reported in the relevant literature. Early recognition affords appropriate management and urgent surgical intervention leading to survival.